A rare ischemic ventricular tachycardia - Gudaghe, Rahul; Deora, Surender (International Journal of Research in Medical Sciences, 2023)
Many times, physicians in emergency may get confronted with tachycardia. Some tachycardia are easily mistaken as supraventricular tachycardia (SVT) with aberrancy which is actually a ventricular tachycardia. So, here we report a case of such tachycardia which was thought to be a SVT but which, in fact, was a ventricular tachycardia instead.